Study on effect of different levels of concentrate on growth performance of both male and female lamb (Asian Journal of Medical and Biological Research, 2016)
The present study was carried out to assess the effect of concentrate on growth performances of both male and female lamb. For this purpose twenty four (12 male and 12 female) lamb aged about 5-6 months were selected and divided into three groups (Treatment group T1, T2 and control group T0). In each group having 4 males and 4 females lamb, all lambs were supplied green roughages ad-libitum, control group T0 was allowed no concentrate and treatment group T1 & T2 were supplied 100 gm & 200 gm concentrate mixture respectively for 90 days experimental period. Animals were weighed at 15 days interval. Significant differences of live weight gain among these three groups were found. Allowing 100 gm (T1) concentrate mixture along with green grass improved growth rate in both male and female lamb. Increasing of concentrate supplementation improved live weight gain (found in T2 group). Total live weight gain (kg) and average daily live weight gain (g/d) were 4.25±0.52 kg and 47.20±5.75 g, 5.38±0.83 kg and 59.73+9.17 g and 7.00±0.54 kg and 77.78±6.00 g in male lambs and 2.25±0.21 kg and 25.00±2.34 g, 3.18±0.32 kg and 35.39±3.63 g and 3.81±0.24 kg and 42.33±2.77 g in female lambs for the To, T1 and T2 groups respectively. Live weight was significantly (P